Limitaciones jurídicas al derecho a la seguridad social de las personas que realizan trabajo no remunerado en el hogar - Albuja Sánchez, Renato Alfredo (2015)
The problem under study and that is the subject of this investigation is aimed at legal analysis of the social security system in Ecuador, so that arises then identified a history of legal dispute; Organic Law of Labor Justice and Labor Award at Home reforming the Labour Code and the Social Security Act was published in the Official Gazette, Third Supplement, No. 483 of April 20, 2015; going to integrate and complement the legislation on labor matters in Ecuador; Among the main points, the rules in question provides for the affiliation to the Ecuadorian Institute of Social Security housewives, constituting in the spirit of the law recognizes the unpaid housework and allowing social protection of beneficiaries or beneficiaries to certain social security rights. For while the beneficiaries are entitled to a retirement pension after serving a minimum of contributions established by law and for as long as required by the same, they are not entitled to benefit comprehensively other privileges such as health care and IESS loans, which represents an impairment of the intangible right to social security; in such a way that it is necessary to consider alternatives to channel the right to social security and comprehensive cash in optimal conditions, with objective to strengthen the universalization of the services provided by the IESS, protecting unrestricted rights of members and especially evaluating and planning adequately to meet the institutional coverage efficiently and effectively contingencies required by the population on social security